2020
DOI: 10.1111/jocs.14472
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of VV ECMO in managing negative pressure pulmonary edema

Abstract: The indications for extracorporeal membrane oxygenation (ECMO) are expanding. Postobstructive pulmonary edema, also known as negative pressure pulmonary edema, can result in severe respiratory compromise and acute respiratory distress syndrome. We present a case of a 26‐year‐old female with laryngeal papillomatosis and laryngospasm after direct laryngoscopy, who developed severe NPPE refractory to mechanical ventilator support, which was successfully treated with veno‐venous ECMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…ECMO is increasingly utilized as a means to provide support for severe pulmonary and/or cardiac failure. The decision to employ ECMO in our case was based on the persistence of refractory hypoxia and a lack of significant improvement with mechanical ventilation 7 . Our experience highlights the successful application of ECMO in managing MAS of sJIA patients presenting with severe respiratory failure unresponsive to standard ventilatory measures.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…ECMO is increasingly utilized as a means to provide support for severe pulmonary and/or cardiac failure. The decision to employ ECMO in our case was based on the persistence of refractory hypoxia and a lack of significant improvement with mechanical ventilation 7 . Our experience highlights the successful application of ECMO in managing MAS of sJIA patients presenting with severe respiratory failure unresponsive to standard ventilatory measures.…”
Section: Discussionmentioning
confidence: 85%
“…The decision to employ ECMO in our case was based on the persistence of refractory hypoxia and a lack of significant improvement with mechanical ventilation. 7 Our experience highlights the successful application of ECMO in managing MAS of sJIA patients presenting with severe respiratory failure unresponsive to standard ventilatory measures. To the best of our knowledge, this is the first report documenting successful remission in ECMOtreated sJIA patients who developed acute pulmonary edema and refractory shock following TCZ infusion.…”
Section: Discussionmentioning
confidence: 87%
“…In the treatment of NPPE, sufficient oxygenation or noninvasive positive pressure ventilation is effective, and reintubation is sometimes necessary in severe cases; however, cases requiring extracorporeal membrane oxygenation have rarely been reported [14][15][16]. The cause of postoperative pulmonary edema is either cardiogenic or noncardiogenic [17].…”
Section: Discussionmentioning
confidence: 99%
“…As aforementioned, patients who have developed upper airway obstruction or have predisposing factors, but have not yet exhibited pulmonary edema, require close observation in the post-anesthesia care unit, although the duration of observation remains controversial ( 1 ). Previously, Grant et al ( 60 ) reported the case of a 26-year-old female patient with laryngeal papillomatosis who developed laryngospasm after direct laryngoscopy. The patient developed severe NPPE, for which mechanical ventilator support was ineffective.…”
Section: Treatmentsmentioning
confidence: 99%